2021
DOI: 10.1186/s13041-021-00832-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of high- and low-spiking regions reveals novel epileptogenic mechanisms in focal cortical dysplasia type II patients

Abstract: Focal cortical dysplasia (FCD) is a malformation of the cerebral cortex with poorly-defined epileptogenic zones (EZs), and poor surgical outcome in FCD is associated with inaccurate localization of the EZ. Hence, identifying novel epileptogenic markers to aid in the localization of EZ in patients with FCD is very much needed. High-throughput gene expression studies of FCD samples have the potential to uncover molecular changes underlying the epileptogenic process and identify novel markers for delineating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 97 publications
2
6
1
Order By: Relevance
“…Interestingly, they found an upregulation of myelin-associated transcripts in FCD cases that had high electric activity, compared with controls from autopsies. In addition, Srivastava et al ( 15 ) found differential expression of lipid-biosynthesis enzymes between FCD and controls, which is similar to our finding concerning cholesterol biosynthesis-enzymes. Despite such similarity, caution is necessary when comparing our data and those from others due to particularities associated with sequencing methods and control selection.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Interestingly, they found an upregulation of myelin-associated transcripts in FCD cases that had high electric activity, compared with controls from autopsies. In addition, Srivastava et al ( 15 ) found differential expression of lipid-biosynthesis enzymes between FCD and controls, which is similar to our finding concerning cholesterol biosynthesis-enzymes. Despite such similarity, caution is necessary when comparing our data and those from others due to particularities associated with sequencing methods and control selection.…”
Section: Discussionsupporting
confidence: 92%
“…The restricted sample size is a limitation of our study. However, it is noteworthy that the number of individuals with FCD is larger than in previous reports (14,15). In addition, despite the reduced sample sizes, we were able to validate the results regarding cholesterol and GPNMB at the protein level, which gives biological consistency to our findings.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations